Prevention of endothelial dysfunction in streptozotocin-induced diabetic rats by Sargassum echinocarpum extract (Medical Journal of Indonesia, 2010)
Aim This study aimed to elicit the protective effect of Sargassum echinocarpum extract on endothelial dysfunction in thoracic aorta of streptozotocin-induced diabetic rats. Methods The animals were divided into 5 groups. The first was normal, the second was diabetic non treated animals. The third to fifth groups were the diabetic animals which given Sargassum echinocarpum extract (150; 300, and 450 mg kg-1 body weight, respectively) by oral gavage and extract treatment was given for 12 weeks. Diabetes was induced by single administration of streptozotocin (45 mg kg-1, i.p.), dissolved in freshly prepared 0.1 M citrate buffer, pH 4.5. Diabetes was confirmed ten days latter in streptozotocin induced animals showing blood glucose levels > 200 mg dL-1 (11.1 mmol L-1) as monitored in the blood from tail vein using glucometer. After the treatment period, the blood serum acquired was used for antioxidant enzymes assays and the thoracic aorta was used for vasorelaxation assay. Results There was a significant decrease in the activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-px) in diabetic rats (3.31 ± 0.12;67.17 ± 0.62;35.10 ± 0.83) comaped to control rats (9.97 ± 0.12;185.31 ± 0.23;116.38 ± 0.88). Administration of Sargassum extract increased the activity of SOD, CAT, and GSH-px. The diabetic rats exhibit endothelial dysfunction as shown by loss of vasodilatory response to acethylcholine (ACH). This was restored by administration of Sargassum extract. Conclusion Sargassum echinocarpum extract ameliorates oxidative stress and reverses the endothelial dysfunction associated with diabetes. This effect appears to be due to its antioxidant properties. (Med J Indones 2010; 19:32-5) Keywords: oxidative stress, sargassum echinocarpum, endothelium dependent relaxation, thoracic aorta